Communications division of BRAC Bank Limited: a 360 degree communication mix for card’s campaign can change customer’s mindset about using cards - Ahmed, MinhajUddin (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.